2016
DOI: 10.1111/jon.12373
|View full text |Cite
|
Sign up to set email alerts
|

The Many Faces of Cerebral Developmental Venous Anomaly and Its Mimicks: Spectrum of Imaging Findings

Abstract: Developmental venous anomalies (DVAs) are the most common cerebral vascular malformations and are usually found incidentally on neuroimaging studies. Despite the benign nature of DVAs, occasionally, they can be symptomatic. The objective of this article is to review the spectrum of imaging findings of DVAs on conventional and advanced imaging studies. In addition, neuroimaging findings of symptomatic DVAs as well as imaging mimicks will also be described to assist in the approach to differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…DVAs draining gray matter were significantly more likely to be hypometabolic than those draining only white matter. These findings support the theory that DVAs produce focal hemodynamic alterations that can result in diminished venous drainage and decrease metabolism in the drainage territory 135–137 . These regional hypometabolism should not be mistaken for a seizure network (Fig 18).…”
Section: Vascularsupporting
confidence: 80%
See 1 more Smart Citation
“…DVAs draining gray matter were significantly more likely to be hypometabolic than those draining only white matter. These findings support the theory that DVAs produce focal hemodynamic alterations that can result in diminished venous drainage and decrease metabolism in the drainage territory 135–137 . These regional hypometabolism should not be mistaken for a seizure network (Fig 18).…”
Section: Vascularsupporting
confidence: 80%
“…Evaluation of DVAs using dynamic susceptibility contrast MR perfusion studies has demonstrated elevation in cerebral blood volume, cerebral blood flow, and delayed time to peak and mean transit time in the brain parenchyma near the DVAs as compared with contralateral parenchyma 134 . These perfusion profiles suggest slow flow, and perhaps increase in perfusion pressure in the region drained by DVA 135 . Moreover, PET scan in the parenchymal adjacent to DVA commonly corresponds to glucose hypometabolism 136,137 .…”
Section: Vascularmentioning
confidence: 99%
“…Arteriovenous malformations – clusters of abnormal arteries and veins with an increased risk of intracranial bleed, more common in young adults [4]. DVAs – most commonly encountered malformation involving the intracranial venous system, which are also known as venous angioma, cerebral venous medullary malformation, or cerebral venous malformation [5]. CCM – vascular spaces of varying sizes, lined by a single layer of endothelin with no distinct features of arteries or veins [6].…”
Section: Intracranial Vascular Malformationsmentioning
confidence: 99%
“…In this scenario, hemosiderin and calcium can be detected. DVAs usually show on MRI flow voids but sometimes only are demonstrated on postcontrast T1‐weighted images, or using SWI, frequently located in the frontal lobes or posterior fossa, often in the vicinity of the ventricular system 27 (Figure 5).…”
Section: Brain Vm Taxonomymentioning
confidence: 99%